Total Lymphocyte Count as a Nutritional Parameter in Hospitalized Patients - Ralph Girson Gunarsa; Marcellus Simadibrata; Ari Fahrial Syam; Ina Susianti Timan; Siti Setiati; Abdul Aziz Rani (The Indonesian Society for Digestive Endoscopy, 2011)
Background: Nowadays, there are still many malnourished patients during hospitalization, which comprises around 45-50% patients. Malnutrition is related to increased mortality and morbidity rate; therefore, nutritional state should be assessed in hospitalized patients. Total lymphocyte count (TLC) is related to decreased body function in malnutrition and it is a means of nutritional assessment. Until now, there is no data showing association between malnutrition and TLC in hospitalized patients in Indonesia. The objective of this study was to identify the association between malnutrition and TLC 1,200 cell/mm3 in hospitalized patients. Method: This study was a cross-sectional study. Subjects were new patients hospitalized at internal medicine ward of Cipto Mangunkusumo Hospital. Patients were collected by consecutive sampling. We conducted the study between April and May 2008. Fifty four patients were assessed for malnutrition by the subjective global assessment (SGA) and they also had undergone complete blood count. TLC was numbered with routine complete blood count test. Patients were classified into malnutrition according to SGA. TLC was classified with cut-off point of 1,200 cell/mm3. Statistical analysis included Chi-square test, which was used to compare proportion. Results: There were 52% malnourished patients, 33% patients with TLC 1,200 cell/mm3, 57% patients with malnutrition and TLC 1,200 cell/mm3. This study showed that there was an association between malnutrition and TLC 1,200 cell/mm3 (p = 0.001). Moreover, there was also significant association between severe malnutrition (SGA C) with TLC 900 cell/mm3 (p = 0.02). Conclusion: There is an association between malnutrition and TLC 1,200 cell/mm3. Keywords: malnutrition, total lymphocyte count, body mass index, subjective global assessment